Cost saving options in drilling and blasting at Subika Pit of Newmont Ahafo Mine, Ghana - Felbah, Isaac Kwesi (University of Mines and Technology, 2018)
Newmont Ahafo Mine (NAM) operates an open pit gold mine in the Brong-Ahafo Region of Ghana. One important cost centre in mining is drilling and blasting. Effective ways of reducing drilling and blasting cost significantly while delivering desired results in fragmentation for shovel loading, hauling and milling was the focus of this research. Drilling and blasting at Newmont Ahafo Mine, open pit operation is generally characterised by drilling patterns parameters in ore and waste zones. Since the start of mine NAM employs a 3 m × 3.5 m blast pattern in its open pit operations. For the year 2017 a 4 m × 4.5 m has been substituted and is intended to deliver better cost savings. In this research, the assessment of cost reduction was testing the cost implication of four blast scenarios in an order of widening the burden and spacing as well as the use of a more potent explosive. Furthermore, comparing their cost over equal areas against the Drill and Blast budget approved for a 3 m × 3.5 m blast pattern. In addition to the old and new blast pattern design parameters at NAM, additional two pattern scenarios were considered and tested to compare the extent of cost savings possible and recommend most prudent parameter accordingly. Four blasts scenarios were tested in all and while three of the four scenarios returned positive results with regards to cost, fragmentation, noise and vibrations, there was a trend of significant cost savings as pattern parameters were widened. There were significant savings, but the optimum pattern of 4 m × 4.5 m pattern currently in use at Newmont Ahafo Mine was elected to save about 46% annually of the Drill and Blast budget for a 3 m × 3.5 m . Recommendation of a research into a possible 4.5 m × 5 m was further recommended for waste zones to further reduce cost was proposed.
vii, 75p. ill.
Keywords: Economic issues; Mine planning; Mining processes